Synovial fluid hydroxyapatite crystals: detection thresholds of two methods. Issue 10 (October 1989) - Cunningham, T; Uebelhart, D; Very, J M; Fallet, G H; Vischer, T L
Abstract : A method of synovial fluid preparation giving optimal hydroxyapatite detection as well as definitions of the threshold masses of hydroxyapatite in viscous synovial fluid detectable by x ray diffraction and scanning electron microscopy with energy dispersive analysis is reported. Use of an equal volume of 100% hydrazine with the synovial fluid optimised detection of hydroxyapatite. By x ray diffraction the threshold mass of hydroxyapatite was 500 micrograms and by scanning electron microscopy with associated energy dispersive analysis 5 micrograms.